Shelf-life extension of green leafy vegetables through minimal processing: Special emphasis on the use of novel techniques - Riya Goel; Darshanjot Kaur; Ravneet Kaur; Kaiser Younis; Ovais Shafiq Qadri (Journal of Agriculture and Food Research)
A key constituent in the shelf-life extension of leafy greens is post-harvest processing. As green leafy vegetables are a crucial part of the diet, their high perishability is a concern. Leafy greens are a rich source of nutrients, vitamins, and antioxidants, and they hold a higher place in the food pyramid. Traditional preservation techniques like thermal processing, drying, and freezing have been unable to provide the desired results, leading to certain disadvantages like microbial spoiling, unwanted residue, and short shelf life. Novel techniques like ultrasound, nanoemulsions, edible coatings, and hurdle technology require minimal processing but provide superior results. The increased shelf-life using minimal processing techniques for various fruits and vegetables has been achieved, but leafy greens are yet to be exploited. The short-term availability of green leafy vegetables is a major challenge to successful shelf-life extension and is thus also an important research area. This review aims to provide detailed insights into the nutritional/medicinal value, as well as minimal processing techniques for shelf-life extension of the leafy greens. It also discusses the major challenges and solutions explored to achieve increased shelf-life of green leafy vegetables.